To The Covid-19 Pandemic Experience: A View from Russia - Maksimov, Maksim (2021)
In the presented work, an attempt to assess the correlation between the performance indicators of several sectors of the Russian economy and a set of restrictive measures taken by the Government of our country against the backdrop of the fight against the COVID-19 pandemic is made.  In addition, a comparative analysis of the impact of this pandemic on the neighboring countries of Russia, which, in the recent past, were part of the USSR and, therefore, have similar health care organization structures, is carried out.